Dinosaur Tracks : The Next Steps - Richter, Annette; Marty, Daniel, 1973-; Falkingham, Peter L. (Book collections on Project MUSE., 2016)
"This book was developed from a dinosaur track symposium that was organized and held in April 2011 in Obernkirchen, Germany, on behalf of the Niedersachsisches Landesmuseum Hannover (Lower Saxony State Museum Hannover)."--